OHP-016 Assessment of pharmaceutical intervention to improve the quality of antibiotics prescribing. (24th February 2014) - De Terline, D; Hue, B; Meynard, JL; Lalande, V; Fernandez, C; Offenstadt, G; Antignac, M
Abstract : Background: The emergence of multiresistant bacteria and their spread has become a public health issue. In 2011, the Anti-Infective Drugs Committee of Saint Antoine Hospital (Paris) established a requirement for a specific prescription for 7 antibiotics (imipenem, doripenem, ertapenem, meropenem, linezolid, tigecycline and daptomycin) in order to restrain the use of these antibiotics. The Committee specially insists on the importance of the antibiotic treatment being reassessed after 72 h by a senior physician or an anti-infectious authority. Purpose: To assess prescription quality and the contribution of a pharmaceutical intervention. Materials and methods: Saint Antoine is a teaching hospital of 760 beds with surgical and medical units including a haematological department. In order to assess the quality of antibiotics prescriptions, two one-month surveys were carried out before and after a pharmaceutical intervention. During these periods, antibiotics prescriptions were exhaustively analysed and data were collected within an Excel table . The intervention: Informed clinical units in writing of the results of the first survey and the wish to improve them. Established pharmaceutical validation: each prescription was analysed by a pharmacist and if needed, he would require modifications. In the second survey, in order to assess whether the improvement in the quality of the prescriptions was attributable to the prescribers' involvement or to the pharmaceutical validation, we collected data before and after modifications required by the pharmacist. Prescription quality was assessed by 5 criteria: Was the indication filled in? Did the physician provide information about initiation or continuation of the treatment? Was the treatment reassessed by a senior physician after 72 h? Was the serum creatinine entered by the physician? Was drug dose appropriate? Results: Results are detailed in the following table : Conclusions: The pharmacist's intervention and physician's involvement have improved the quality of prescriptions; results have undoubtedly improved between the two surveys. Every antibiotic prescription is henceforth systematically validated by a pharmacist. The next step is to establish a multidisciplinary cell to validate the indication. No conflict of interest.